External causes and maternal mortality: proposal for classification - Alves, Mercia Maria Rodrigues; Alves, Sandra Valongueiro; Antunes, Maria Bernadete de Cerqueira; Santos, Dirce Luiza Pereira dos (Revista de Saúde Pública, 2013)
OBJECTIVE To analyze deaths from external causes and undefined causes in women of childbearing age occurring during pregnancy and early postpartum. METHODS The deaths of 399 women of childbearing age, resident in Recife, Northeastern Brazil, in the period 2004 to 2006, were studied. The survey utilized the Reproductive Age Mortality Survey method and a set of standardized questionnaires. Data sources included reports from the Institute of Legal Medicine, hospital and Family Health Strategy records and interviews with relatives of the deceased women. External causes of death during pregnancy were classified according to the circumstance of death, using the O93 code (ICD) and maternal mortality ratios before and after the classification were calculated. RESULTS Eighteen deaths during pregnancy were identified. The majority were aged between 20 and 29, had between 4 and 7 years of schooling, were black and single parents. Fifteen deaths were classified using the O93 code as pregnancy related death (13 for homicide – code 93.7; 2 by suicide – code 93.6) and three were classified as indirect obstetric maternal deaths (one homicide – code 93.7 and two by suicide – code 93.6). There was an average increment of 35% in the RMM after classification. CONCLUSIONS Deaths from undefined causes in and in early postpartumdid not occur by chance and their exclusion from the calculations of maternal mortality indicators only increases levels of underreporting.